PENGARUH DIGITALISASI SISTEM PERUSAHAAN TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA SEBAGAU VARIABEL INTERVENING (STUDI PADA PT. BANK NEGARA INDONESIA KANTOR WILAYAH SEMARANG) - Mochammad Farrel Shidqi; Ismi Darmastuti; Bimo Suryo Wicaksono (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT This study aims to determine and analyze how the effect of digitizing the company's system on job satisfaction, in addition, to whether the digitalization of the company's system influences employee performance, to find out whether job satisfaction has an influence on employee performance, and to find out whether job satisfaction mediates positively and significantly the effect digitalization of company systems on employee performance. The measuring instruments used in this study were closed questioner. This study uses a purposive sampling approach technique where this technique is a sampling technique. The result of this study is the digitization of the company's system has a positive and significant effect on job satisfaction. The digitization of the company's system has no direct effect on employee performance. Job satisfaction has a positive and significant effect on employee performance. Based on the Sobel test, job satisfaction mediating the digitization of the company's system on employee performance has a positive and significant effect. Digitalization of the company's system has a strong influence on employee performance through job satisfaction. Digitizing the company's system can be said to be good if it can help and facilitate the work of employees.